2022
DOI: 10.21037/jtd-22-486
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless aortic valve replacement in high-risk patients with active infective endocarditis

Abstract: Background: Surgical aortic valve replacement remains the gold standard of treatment in patients with active infective endocarditis. Such procedures tend to carry a significantly higher operative risk when compared to the conventional aortic valve replacement for a non-infective aortic valve disease. Sutureless aortic valve replacement (SU-AVR) has been introduced into cardiac surgery to allow for a simpler implementation of minimally invasive procedures. Although SU-AVR in several extended indications has pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Similarly, in the previously cited recent study by Zubarevich et al [7], the authors reported in their series of 13 patients a mean CPB and AXC times of 89.8±33.6 minutes and of 59.1±27.8 minutes, respectively. Not only many of the patients with IE are too sick to sustain long morbid operations, but also these patients would probably benefit the most from a hemodynamically good postoperative valvular performance and a low rate of PVL.…”
Section: Smoaj000606 5(2)2023supporting
confidence: 65%
See 1 more Smart Citation
“…Similarly, in the previously cited recent study by Zubarevich et al [7], the authors reported in their series of 13 patients a mean CPB and AXC times of 89.8±33.6 minutes and of 59.1±27.8 minutes, respectively. Not only many of the patients with IE are too sick to sustain long morbid operations, but also these patients would probably benefit the most from a hemodynamically good postoperative valvular performance and a low rate of PVL.…”
Section: Smoaj000606 5(2)2023supporting
confidence: 65%
“…Even in this appalling scenario, our observed 30-d mortality was 13.9% and the 1-year survival exceeded the 72%. Recently, Zubarevich et al [7] have published a series 13 patients undergoing SU-AVR because of a complicated aortic IE. In that study, the authors reported a 30-d mortality of 23.1%, yet the expected mortality estimated by the logistic EuroSCORE I and EuroSCORE II was 47.9%±23.1% and 28.7%±22.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Both Weymann et al and Zubarevich et al have described their experience with Perceval S use in 9 and 13 patients with IE, respectively. 54 , 55 Early postoperative results have been promising, with low mortality, no required PPI, and satisfactory valve hemodynamics upon discharge. However, 3-month and 6-month mortality rates of 23.1% and 46.2%, respectively, do raise some concerns, but it is important to note that these were very high-risk patients, with the majority having a history of previous cardiac surgery and requiring concomitant procedures.…”
Section: Resultsmentioning
confidence: 99%
“…However, 3-month and 6-month mortality rates of 23.1% and 46.2%, respectively, do raise some concerns, but it is important to note that these were very high-risk patients, with the majority having a history of previous cardiac surgery and requiring concomitant procedures. 54 SUAVR in patients with IE appears feasible; however, much more investigation is ultimately required prior to the more widespread adoption of this practice.…”
Section: Resultsmentioning
confidence: 99%
“…The latter could hypothetically contribute to its’ lower susceptibility to infectious processes ”. Based on this hypothesis, their aim was to examine the feasibility of SU-AVR in 13 consecutive high-risk patients with active infective aortic valve endocarditis ( 1 ).…”
mentioning
confidence: 99%